Volterra’s theory of elastic dislocations for a transversally isotropic homogeneous hollow cylinder - Laserra, E.; Pecoraro, M. (Нелінійні коливання, 2003)
This work will consider Volterra’s theory of elastic dislocations in the case of a transversally isotropic homogeneous hyperelastic hollow cylinder. We obtain explicit equations for vector field of displacements, for tensor fields of strain and stress, and for forces upon the boundary.